New Zealand English Grammar - Fact or Fiction?: A corpus-based study in morphosyntactic variation - Hundt, Marianne (Varieties of English Around the World, 1998)
New Zealand English (NZE) is one of the younger post-colonial varieties of English. It is therefore not surprising that previous research focused on lexical and phonological aspects of NZE and practically neglected grammatical peculiarities. New Zealand English Grammar - Fact or Fiction? presents a careful comparative analysis of parallel corpora of New Zealand, British, American and Australian English in order to single out morphological, syntactic and lexico-grammatical features typical of an emerging New Zealand standard. In addition to corpus data on regional variation, the author uses data on short-term diachronic change within British and American English to show how regional variation is closely related to both stylistic variation (a world-wide colloquialisation of the written norms of English) and ongoing linguistic change leading to temporal regional differences. NZE is different from other national varieties of English in terms of preferences for certain variants rather than categorically different grammatical rules. Nevertheless, it is a standard in its own right in so far as it is a typical mix of variants available in World English. The methodological approach combines both qualitative analyses and statistical evidence. The question in how far statistically significant differences in word frequencies can be shown to be linguistically significant is also relevant for other quantitative research into emerging national standards.